2011
DOI: 10.1002/bdra.20840
|View full text |Cite
|
Sign up to set email alerts
|

The CRISPLD2 gene is involved in cleft lip and/or cleft palate in a Chinese population

Abstract: Our results suggest that the CRISPLD2 gene contributes to the etiology of NSCLP in the Northwestern Chinese population. SNP rs1546124 is significantly related to NSCLP, associated with both CL/P and CPO groups, and SNP rs4783099 is significantly associated with CPO.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
29
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 36 publications
3
29
0
Order By: Relevance
“…There are however intriguing associations between the paralogue, CRISPLD2 and non-syndromic cleft lip with or without cleft palate Chiquet et al, 2007;Letra et al, 2011;Shen et al, 2011;Shi et al, 2010). We found that CRISPLD2 was enriched in the normal frontonasal mass (3.0 fold) which expands the limited expression analysis presented in the original study (Chiquet et al, 2007).…”
Section: Pi15 and The Relationship To Orofacial Cleftingsupporting
confidence: 67%
“…There are however intriguing associations between the paralogue, CRISPLD2 and non-syndromic cleft lip with or without cleft palate Chiquet et al, 2007;Letra et al, 2011;Shen et al, 2011;Shi et al, 2010). We found that CRISPLD2 was enriched in the normal frontonasal mass (3.0 fold) which expands the limited expression analysis presented in the original study (Chiquet et al, 2007).…”
Section: Pi15 and The Relationship To Orofacial Cleftingsupporting
confidence: 67%
“…Interestingly, a recent report showed a decreasing risk of facial clefts in individuals with same SNP genotype among Han Chinese population [15]. In agreement with our study, Shen et al also found significant difference in genotype and allele frequencies of rs1546124 (OR = 2.30; 95%, CI = 1.58-3.34; P < 0.001) in nsCL/P patients compared with controls [6]. In contrast, a family-based study from Italian population revealed no association between rs1546124 allele or genotype and ns/CLP [8].…”
Section: Discussionsupporting
confidence: 92%
“…In the present study, 18 CRISPLD2 SNPs were evaluated in 380 individuals. Our case-control study showed evidence for association between the CRISPLD2 gene and ns/CLP in this Xinjiang Uyghur population, providing further support to the previous findings of Chiquet et al [5], Shen et al [6], and Shi et al [20] that CRISPLD2 is involved in the pathogenesis of ns/CLP. The locus rs1546124, one of the most investigated markers of the CRISPLD2 gene is located in exon2, 51 bp upstream of the ATG start codon.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations